PERANAN STRATEGI WORD OF MOUTH MARKETING DALAM PENJUALAN BATIK MOTIF SUMATERA UTARA (Studi pada UD. Mitra Cahaya Jl. Letda Sudjono Gg. Al Halim Kiri No. 1 Kecamatan Medan Tembung, Kota Medan) - Charisma Parhimpunan Agung Pasaribu (Jurnal Niaga & Bisnis (e-journal), 2014)
The purpose of this research was to analyze the role of word of mouth marketing strategy in selling batik theme of North Sumatera  UD. Mitra Cahaya and analyze the effectiveness of word of mouth marketing strategy in selling batik theme of North Sumatera UD. Mitra Cahaya. In addition, the purpose of this research was to find another alternative marketing communication strategies to do UD. Mitra Cahaya in the sale of batik theme of North Sumatera. In this research, the method used is descriptive method with qualitative approach. Informants in this research are divided into three groups. Key informant is the owner of UD. Mitra Cahaya, mayor informant is manager of UD. Mitra Cahaya and additional informant is consumers of UD. Mitra Cahaya. Data collections techniques used in the first two kinds of primary data collection techniques by conducting observation and interviews, while the second is the secondary data collection techniques with the collection of literature and documentation. Data analysis techniques used in this research is descriptive data analysis techniques. Based on the results of the research, the role of word of mouth marketing strategy has been going well and is very effective in the sales of batik theme of North Sumatera UD. Mitra Cahaya. It can be seen where consumers tell, promote, recommend and sell batik theme of North Sumatera to other prospective customers. Consumers who do this are satisfied with the batik theme of North Sumatera UD. Mitra Cahaya. Reseacher has found another alternative marketing communication strategies that can be done by UD. Mitra Cahaya is to do the packaging in the form of catalog, brochures, business cards, banners, billboards, ads and interesting jargon. Keywords : Word of mouth marketing, marketing communication, selling